Positive displacement pumps : (John Wiley & sons, 2007)
Prepared by the Equipment Testing Procedures Committee of the American Institute of Chemical Engineers, this manual provides pump users with concise, easy to read, illustrated field-testing procedures for testing various types of pumps in the field--gear, lobe, multiple screw, vane, progressive cavity, diaphragm, piston/plunger--taking into account the imperfect realities of actual field conditions. It includes definitions of major terms, conversion factors, and nomenclature; descriptions of test preparation logistics, safety precautions, instruments, methods of measurement, standardized tests, and other tests; and coverage of pump-testing applications handling non-Newtonian fluids. For chemical engineers, plant managers, and other professionals responsible for evaluating positive displacement pumps. Illustrated throughout with b&w diagrams, tables, and charts.